2020
DOI: 10.3390/life10080150
|View full text |Cite
|
Sign up to set email alerts
|

Protoenzymes: The Case of Hyperbranched Polymer-Scaffolded ZnS Nanocrystals

Abstract: Enzymes are biological catalysts that are comprised of small-molecule, metal, or cluster catalysts augmented by biopolymeric scaffolds. It is conceivable that early in chemical evolution, ancestral enzymes opted for simpler, easier to assemble scaffolds. Herein, we describe such possible protoenzymes: hyperbranched polymer-scaffolded metal-sulfide nanocrystals. Hyperbranched polyethyleneimine (HyPEI) and glycerol citrate polymer-supported ZnS nanocrystals (NCs) are formed in a simple process. Transmission elec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 73 publications
0
15
0
Order By: Relevance
“…For example, replacement of citric acid in the ternary starting mixture with methylsuccinic acid or adipic acid also resulted in similar hyperbranched polyester products, which even had the ability to act as catalysts to the Kemp elimination reaction by increasing the reaction rate by two- to three-fold, thus suggesting that polyesters with sufficient chemical, structural, and functional complexity could have been early catalysts (i.e., “protoenzymes”) on early Earth before the emergence of peptide or protein-based catalysts [ 51 ]. Further development of this system revealed that hyperbranched polyesters could even scaffold photocatalytic zinc sulfide nanoparticles [ 53 ]. However, other than the literature described here, there are not many studies which focus on prebiotic hyperbranched polyesters, and we suggest that this should be a priority for future study.…”
Section: Membraneless Polyester Protocellsmentioning
confidence: 99%
“…For example, replacement of citric acid in the ternary starting mixture with methylsuccinic acid or adipic acid also resulted in similar hyperbranched polyester products, which even had the ability to act as catalysts to the Kemp elimination reaction by increasing the reaction rate by two- to three-fold, thus suggesting that polyesters with sufficient chemical, structural, and functional complexity could have been early catalysts (i.e., “protoenzymes”) on early Earth before the emergence of peptide or protein-based catalysts [ 51 ]. Further development of this system revealed that hyperbranched polyesters could even scaffold photocatalytic zinc sulfide nanoparticles [ 53 ]. However, other than the literature described here, there are not many studies which focus on prebiotic hyperbranched polyesters, and we suggest that this should be a priority for future study.…”
Section: Membraneless Polyester Protocellsmentioning
confidence: 99%
“…Hygroscopic salts also sequester water [ 39 ]. These environments enable unique aqueous-phase chemistries such as the synthesis of polymer-supported zinc sulfide nanocrystals [ 40 ] or photochemical phosphorylation [ 38 ], and can also reduce evaporation rates and prevent total desiccation.…”
Section: Prebiotic Microenvironments and Where To Find Themmentioning
confidence: 99%
“…For example, hyperbranched polymers have been shown to be able to scaffold the assembly of zinc sulfide nanocrystals. [ 172 ] For example, perhaps polymeric gel compartments could have actively scaffolded lipid assembly on its surface [ 127 ] to promote the formation of an enclosing membrane. This ability for a membraneless droplet to actively acquire and assemble a lipid membrane could have been a key stage of evolution connecting a membraneless protocellular world (polymeric gel material droplets) to a membrane‐bound world (more cell‐like state).…”
Section: A Potential Material‐based Panspermia Modelmentioning
confidence: 99%
“…However, some gels have been found to be more heat‐resistant than others, namely hyperbranched polymer gel‐based materials, [ 197 ] some of which appear to be stable >850 °C [ 198 ] ; as mentioned before, hyperbranched gel‐based polymers have been investigated in the context of OoL and prebiotic chemistry. [ 167,172 ] Although this would still be far less than the maximum temperatures reached by particles upon atmospheric entry, not all particles reach the maximum temperature, and a recent study suggested that the average entry temperature of micrometeorites to Earth (radius of <~1 mm) was closer to 1300 °C, rather than 2000 °C. [ 199 ] In fact, it was proposed that 3.5% of all such micrometeorites would not reach 900 °C during entry into the Earth atmosphere [ 199 ] ; if entry of M‐BPS onto a receiving planet with an Earth‐like atmosphere resulted in similar entry temperatures of the gel materials, then at least some percentage of the materials could have arrived onto the planet surface in‐tact.…”
Section: Open Questions and Limitation To The Material‐based Pansperm...mentioning
confidence: 99%